(untitled) (Actualizaciones en Sida e Infectología, 2025)
This article presents an analysis of four human cases of Western Equine Encephalitis (WEE) in Viedma during 2024, which required hospitalization in two complex medical centers. Neurological symptoms, diagnostic methods, and patient outcomes are examined, revealing that the disease can have a severe prognosis. It is suggested that this diagnosis should be considered in patients suspected of equine encephalitis who present with meningoencephalitis without a clear etiology, despite the absence of a distinct epidemiological link. The conclusion emphasizes that surveillance, vector control, vaccination of equines, and education on prevention are essential to address the reemergence of WEE, as well as the importance of a multidisciplinary response to improve the detection and management of cases.